Perlindungan Hukum Bagi Korban Malapraktik Oleh Klinik Kecantikan Zevmine Pure Beauty Skin Care Berdasarkan Undang-Undang No. 8 Tahun 1999 Tentang Perlindungan Konsumen Juncto Undang-Undang No. 36 Tahun 2009 Tentang Kesehatan - Rakhmatullah, Anne Gunawati, Dede Agus, Mohamad Fakih (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
A beauty clinic is a place of service for one's appearance needs in getting beauty and health for the skin and body. However, in practice it does not always go as expected, malpractice acts often occur, namely errors or negligence on the part of medical personnel (doctors) as business actors in carrying out their health services as in the case of the Zevmine Pure Beauty Skin Care Beauty Clinic, this causes losses to the victim as consumers of health services. Based on this background, it is necessary to study how legal protection is for victims of malpractice by beauty clinics and what is the responsibility of business actors towards victims of malpractice by zevmine pure beauty skin care beauty clinics based on Law no. 8 of 1999 concerning Consumer Protection Juncto Law no. 36 of 2009 concerning Health. The research method used is normative juridical with a statutory approach, conceptual approach and case approach. The data used is secondary data and is supported by primary data, and analyzed descriptively qualitatively. The research results show that legal protection for victims of malpractice by beauty clinics has not been implemented optimally and comprehensively. The responsibilities of the Zevmine Pure Beauty Skin Care Beauty Clinic have not been carried out optimally, business actors only provide advice on giving painkillers and neutral injections to the victim's body parts as well as providing material compensation, but this has not been fully implemented, there are still many responsibilities that have not been carried out. given to victims of malpractice as regulated in Article 4, Article 5, Article 7, Article 8 paragraph (1), Article 29 and Article 30 of Law no. 8 of 1999 concerning Consumer Protection Juncto Article 58 of Law no. 36 of 2009 concerning Health, and the sanctions that can be imposed on business actors are criminal sanctions in the form of imprisonment or fines and administrative sanctions in the form of written warnings or revocation of operational permits.